1997
DOI: 10.1177/000348949710600406
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Esophagoscopy in the Irradiated Esophagus

Abstract: Carcinoma of the esophagus is a disease with a poor prognosis. Surgery is considered the treatment of choice. Patients who are surgically unresectable may receive radiotherapy, plus or minus chemotherapy. While this offers reasonable palliation, a significant number of patients develop benign or malignant strictures. Frequent esophagoscopy with dilation is required if they are to swallow. Patients with strictures or malignancy of the esophagus are more prone to complications if they undergo an esophagoscopy. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…An upper gastrointestinal series three weeks after dilation did not reveal a fistula, suggesting that dilation was not causative. Previous studies have shown that esophageal dilation can be safely performed after radiotherapy [19,20], without increased risk of perforation [19]. …”
Section: Discussionmentioning
confidence: 99%
“…An upper gastrointestinal series three weeks after dilation did not reveal a fistula, suggesting that dilation was not causative. Previous studies have shown that esophageal dilation can be safely performed after radiotherapy [19,20], without increased risk of perforation [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Spinal epidural abscess is one such very rare but potentially catastrophic infective complication. A literature search identified only five case reports of spinal epidural abscess following esophageal perforation [2][3][4][5][6]. In these cases, the causes of esophageal perforation were iatrogenic esophageal instrumentation in three cases [2][3][4] and blunt trauma in association with spinal fracture in two cases [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Mediastinal sepsis progressing to spinal epidural abscess is an even rarer complication of esophageal perforation [2][3][4][5][6]. Both esophageal perforation and spinal epidural abscess require prompt treatment to avoid a disastrous outcome [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%